2021
DOI: 10.1590/1517-8692202127072021_0347
|View full text |Cite
|
Sign up to set email alerts
|

Eeg and Central Nervous System Transmitter on Athletes Training

Abstract: Introduction: Modern EEG technology can evaluate the current level of an individual's central functioning after analyzing the frequency of brain waves (II). The A wave (8 ~ 14Hz) of brain waves (EBG) is one of the most important index parameters in diagnosing the brain's central functioning level. Objective: To explore the effects of different training loads on the brain function of elite archers and provide an objective basis for improving the scientific level of archery training. Methods: The effects of EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Complexity has also become a hot topic in exercise science research ( Wang et al, 2019 ; Zhu, 2021 ) and is often employed as an important reference index for elucidating the central nervous system mechanisms underlying exercise performance. Research has shown that exercise training can effectively reduce the complexity level of the brain and complexity is negatively correlated with exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…Complexity has also become a hot topic in exercise science research ( Wang et al, 2019 ; Zhu, 2021 ) and is often employed as an important reference index for elucidating the central nervous system mechanisms underlying exercise performance. Research has shown that exercise training can effectively reduce the complexity level of the brain and complexity is negatively correlated with exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…Bieru et al (2021) used EEG to record the brain activity of 12 judo athletes and 11 volleyball athletes during hand flexor contraction and relaxation, which helps coaches evaluate the training effect of athletes [9]. Zhu (2021) assessed the impact of EEG information and central nervous transmission on athletes' regulation and training, providing a basis for improving the level of archery training [10].…”
Section: Introductionmentioning
confidence: 99%